Selection of F4 progenies of ornamental peppers (Capsicum annuum L.) using multivariate methods - do Perpetuo Socorro Damasceno Costa, Maria; Ramalho do Rêgo, Elizanilda; Alves Barroso, Priscila; Gonçalves de Carvalho, Michelle; Monteiro do Rêgo, Mailson (Revista Ceres, 2024)
Although peppers show genetic diversity, there are few ornamental cultivars in Brazil. The purpose of this study was to evaluate the genetic diversity between progenies from F4 populations of peppers. Ten progenies were evaluated, each with 45 plants, and 4 additional control with 15 plants. Sixteen quantitative plant and fruit descriptors were used. The data were subjected to multivariate analysis of variance, and relative importance was determined using Singh’s method. Canonical variable analysis and the Scott-Knott test were used to evaluate the association between characteristics and/or individuals. In addition, non-metric multidimensional scaling was applied. The multivariate analysis of variance for the quantitative characters showed that there were significant differences. The Singh method determined that six of the fifteen characteristics contributed with more than 80.00% of the genetic divergence, while nine characteristics contributed with only 18.70%. In the analysis of canonical variables, the first two canonical variables explained 70.42 % of the discrimination between families and using the ScottKnott test the progenies were grouped into 8 groups. The non-metric multidimensional scaling method separated the progenies from the control. Progenies that showed the desirable characteristics for potted ornamentals were 4, 8, 9 and 10. Selection within these progenies is recommended to continue the ornamental pepper breeding program.